ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS LAYANAN SHOPEE - Asogi Akbar (Scientium Management Review, 2022)
The Covid-19 pandemic caused many people starting to switch to buying and selling online, some of them use Shopee e-commerce. The aim of this study is to analyze the factors that influence customer satisfaction with service quality and to analyze Shopee's service quality using confirmatory factor analysis and e-servqual analysis. The variables of this study are divided into seven dimensions of e- servqual, namely efficiency, fullfilment, system avaibility, privacy, responsiveness, compensation, and contact, with a total of 23 indicators. This study took a sample of 126 Shopee user respondents in Bali Province who had made transactions at least 3 times until 2021. The results of the factor analysis show that there really are seven dimensions that affect the quality of online services. The results of the e-servqual analysis obtained the value of consumer perceptions of service quality is 7.82 , this value was included in the satisfied category. The factors that require focus of attention are the dimensions of system availability, need to improve the system so that the server does not down easily during heavy traffic.